A case-control study of childhood leukaemia and paternal occupational contact level in rural Sweden - Kinlen, L; Jiang, J; Hemminki, K (2002)
In a national case-control study in Sweden, we investigated whether in rural areas (where susceptible individuals are more prevalent than in urban areas) leukaemia risk was higher among the young children of fathers with many work contacts, as the infective hypothesis has predicted. A total of 1935 cases diagnosed in 1958-1998 together with 7736 age-matched (within 1 year) population controls (of whom 970 and 3880 respectively were aged 0-4) were linked to paternal occupational details as recorded in the census closest to the year of birth. Applying the two classifications of occupational contact revel used in a study of rural Scotland, the odds ratios for children aged 0-4 years in the highest contact category (which includes teachers) in the most rural Swedish counties were 3.47 (95% Cl 1.54, 7.85) and 1.59 (1.07, 2.38) respectively, relative to the medium and low (reference) category; no such excess was found in urban or intermediate counties. There was also a significant positive trend at ages 0-4 in the rural counties across the three levels of increasing occupational contact (P for trend 0.02 and 0.03, respectively), but again not in the urban or intermediate counties. No such effect or trend was found at ages 5-14 in any of the three county groupings. The findings confirm those of a recent study in rural Scotland, and also suggest that unusual population mixing (as occurred in Scotland as a result of the North Sea oil industry) is not a necessary requirement for the effect, since comparable mixing has not been a feature of rural Sweden. © 2002 Cancer Research UK.